Efforts of the Head of Madrasah MIS Raudlatul Atfal 3 in Improving Student Reading Literacy Based on AKMI Results in 2023 - Anwar, Ach.; Hidayatillah, Yetti; Ikmal, Moh. (Electronic Journal of Education, Social Economics and Technology, 2024)
This study explores the efforts of the principal of MIS Raudlatul Athfal 3 to enhance students' competencies based on the 2023 Indonesian Madrasah Competency Assessment (AKMI) results. The AKMI outcomes revealed varied student achievements, with most categorized as "Competent" (CK 3), while some remained at the "Basic" (CK 2) level, particularly in reading and science literacy. Key challenges included limited resources such as reading materials and teaching aids. To address these gaps, the principal implemented various strategies, including the integration of the School Literacy Movement through reading corners, pre-lesson reading policies, and literacy-based learning optimization. A qualitative descriptive method was employed to analyze the 2023 AKMI results and the principal's strategic measures. This study highlights the critical role of school leadership in fostering literacy culture and student competencies to support the development of high-quality human resources.